Складні сучасні процеси інтеграції міжнародного, зарубіжного та національного законодавств - Стрельцов, Євген Львович; Стрельцов, Евгений Львович; Streltsov, Ievgen Lvovych (Харків : Тім Пабліш Груп, 2016)
У статті аналізуються складні сучасні процеси правової інтеграції положень міжнародного, зарубіжного та національного законодавства на прикладі законодавства про кримінальну відповідальність. Звертається увага на спільні та відмінні аспекти такого взаємопроникнення, виділяються обов’язкові ознаки цього. Поряд із традиційними поглядами розглядаються і сучасні спроби такої інтеграції, що дає змогу запропонувати для обговорення змістовні підходи до виділення відповідних груп злочинів. Підкреслюється необхідність «взаємної» правової інтеграції.

В статье на примере уголовного законодательства анализируются современные проблемы правовой интеграции. Наряду с выделением традиционных групп таких преступлений предлагаются и новые подходы к проведению такой интеграции.

Complex events that take place at the present time on the global level, in the region or any state, irrespectively from their content and direction, require the existence of necessary base for their regulation in the general sense of this term. Due to the fact that such events can have different in its “geographical” nature, it should include the relevant provisions of international, foreign and national legislation. To counteract criminal manifestations this should occur at all and at the stated levels of criminal legislation. It should be noted that we have sufficient experience in criminal legislation. However, the dynamics of these processes in space, including the negative content, require addressing to this problem at the modern stage of perfection of such a base. Analysis of recent research and publications. The complexity of such a study has a number of circumstances, which are largely related to the timing of development of the criminal legislation, to different branches of legislation that regulate such processes: international, international and criminal, national. Among Ukrainian specialists who have studied these and similar problems, we should point out: I. P. Bakhnovska, M. V. Buromenskyi, N. A. Zelinska, A. A. Muzyka, V. A. Navrotskyi, A. A. Zhytnyi, V. I. Rolinskyi, A. V. Savchenko, D. I. Krupko, M. I. Khavroniuk and others. Despite the usefulness of these studies, modern processes require additional special addressing to this problem. The main part. The author of the article analyzes the problems of consistent establishment of criminal liability for several groups of international socially dangerous acts, in particular for international crimes and crimes of international nature. Special attention is paid to the fact that recently rather new types of crimes, first of all, the so-called “conventional” are allocated from these and other groups according to a variety of formal and content features. The notion of these crimes, their features and their correlation with existing types of crimes has been revealed. Attention is paid to the possible controversial provisions related to their evaluation. Conclusions. The study of this problem led to the following conclusions. The complexity of the impact on the negative processes that currently take place at all levels of human coexistence, including on the crime, requires a whole range of interrelated activities. The first is the development of the necessary legal base at the international level, the level of foreign countries, the national level. The second, the existence of such legal provisions in international and foreign criminal legislation should be objectively assessed in each democratic state, and therefore necessary measures must be taken before including them into national legislation and conditions for their effective legal implementation must be created. The provisions set out in this article both study this problem and also invite to further scientific discussion.
Сложные современные процессы соотношения международного, иностранного и национального законодательства
Complex Modern Processes of Integration of International, Foreign and National Legislation
Стрельцов Є. Л. Складні сучасні процеси інтеграції міжнародного, зарубіжного та національного законодавств / Є. Л. Стрельцов // Вісник Кримінологічної асоціації України : зб. наук. праць / Харків. нац. ун-т внутріш. справ, Кримінологічна Асоц. України. – Харків, 2016. – № 1. – С. 42-53.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; правова інтеграція; публічне право; міжнародне, зарубіжне, національне кримінальне законодавство; правовая интеграция; публичное право; международное, иностранное, национальное уголовное законодательство; legal integration; public law; international, foreign, national criminal legislation